PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN CANVA TERHADAP HASIL BELAJAR PESERTA DIDIK DI SEKOLAH DASAR - Nurul Fazriyah; Amalia Yulianti; Aas Saraswati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine the effect of using Canva-based learning media on student learning outcomes in elementary schools. In this study using a quantitative approach with a research design that is quasi experimental (quasi experimental design). The sample in this study was the VA class, which consisted of 24 students as the experimental class and the VB class, which consisted of 22 students as the control class. Data collection techniques through tests and observations. The tests used are tests using the pre-test and post-test which are used as data on student learning outcomes. Based on the results of the study, in the experimental class, the average pre-test score of students was 50.75 and the average post-test score of students was 84.87. Whereas in the control class, the average pretest score for students was 43.32, and the average post-test score for students was 70.95. The results of the calculation test in the experimental class and control class, it can be concluded that the post test scores are greater than the pretest values, meaning that there is an increase in student learning outcomes. The researcher used an independent sample t test to find the effect of using Canva-based learning media on student learning outcomes in elementary schools. It is known that the calculated t value of 7.851 > 2.069 has a sig of 0.000 <0.05, which means that there is a significant influence on the learning outcomes of students in the experimental class and control class. Then in accordance with the decision making determined that H0 is rejected and Ha is accepted. So, thus the researchers concluded that the effect of using Canva-based learning media on the learning outcomes of students in elementary schools.